Factors Predicting Atypical Development of Nighttime Bladder Control. Issue 9 (November 2015) - Sullivan, Sarah; Joinson, Carol; Heron, Jon
ABSTRACT: Objective: To derive latent classes (longitudinal "phenotypes") of frequency of bedwetting from 4 to 9 years and to examine their association with developmental delay, parental history of bedwetting, length of gestation and birth weight. Method: The authors used data from 8, 769 children from the UK Avon Longitudinal Study of Parents and Children cohort. Mothers provided repeated reports on their child's frequency of bedwetting from 4 to 9 years. The authors used longitudinal latent class analysis to derive latent classes of bedwetting and examined their association with sex, developmental level at 18 months, parental history of wetting, birth weight, and gestational length. Results: The authors identified 5 latent classes: (1) "normative"—low probability of bedwetting; (2) "infrequent delayed"—delayed attainment of nighttime bladder control with bedwetting <twice a week; (3) "frequent delayed"—delayed attainment of nighttime bladder control with bedwetting ≥ twice a week; (4) "infrequent persistent"—persistent bedwetting < twice a week; and (5) "frequent persistent"—persistent bedwetting ≥ twice a week. Male gender (odds ratio = 3.20 [95% confidence interval = 2.36–4.34]), developmental delay, for example, delayed social skills (1.33 [1.11–1.58]), and maternal history of wetting (3.91 [2.60–5.88]) were associated with an increase in the odds of bedwetting at 4 to 9 years. There was little evidence that low birth weight and shorter gestation period were associated with bedwetting. Conclusion: The authors described patterns of development of nighttime bladder control and found evidence for factors that predict continuation of bedwetting at school age. Increased knowledge of risk factors for bedwetting is needed to identify children at risk of future problems attaining and maintaining continence. Abstract : This article has supplementary material on the web site: www.jdbp.org.